Material application, performance and life cycle - Sulaiman, Shamsuddin (Elsevier, 2015)
This featured article gives a brief outline of what to expect in this section titled “Materials Application, Performance and Life Cycle” of the Reference Module in Material science and Materials Engineering. The scope of the section is very wide due to the wider application areas and types of materials that are available to us. The articles which will be presented will therefore include application of structural materials like, steel, aluminum alloys, concrete, timber, glass, ceramics, composites etc. relevant to all form of buildings, aircrafts, domestic dwellings, machine components, domestic appliances, novelty goods, toys and so on. The section will also include articles which deal with important aspect of materials, namely, performance in service, property evaluation, design for critical functionality, service life evaluation, remnant life and failure prediction. Some articles will delve into the aspect of safety and environmental effect in connection with disposal and recycling of these materials.